The military and denied development in the Pakistani Punjab : an eroding social consensus - Khan, Shahrukh Rafi; Akhtar, Aasim Sajjad; Bodla, Sohaib (Anthem frontiers of global political economy., 2014)
This book explores retrogressive agrarian interventions by Pakistan's military in the Punjab and details the social resentment and resistance it has initiated.